Integration of migrant and refugee data in health information systems in Europe: advancing evidence, policy and practice - Bozorgmehr, Kayvan; McKee, Martin; Azzopardi-Muscat, Natasha; Bartovic, Jozef; Campos-Matos, Ines; Gerganova, Tsvetelina-Ivanova; Hannigan, Ailish; Janković, Jelena; Kállayová, Daniela; Kaplan, Josiah; Kayi, Ilker; Kondilis, Elias; et al. (The lancet. Regional health, 2023)
Coverage of migrant and refugee data is incomplete and of insufficient quality in European health information systems. This is not because we lack the knowledge or technology. Rather, it is due to various political factors at local, national and European levels, which hinder the implementation of existing knowledge and guidelines. This reflects the low political priority given to the topic, and also complex governance challenges associated with migration and displacement. We review recent evidence, guidelines, and policies to propose four approaches that will advance science, policy, and practice. First, we call for strategies that ensure that data is collected, analyzed and disseminated systematically. Second, we propose methods to safeguard privacy while combining data from multiple sources. Third, we set out how to enable survey methods that take account of the groups’ diversity. Fourth, we emphasize the need to engage migrants and refugees in decisions about their own health data. Based on these approaches, we propose a change management approach that narrows the gap between knowledge and action to create healthcare policies and practices that are truly inclusive of migrants and refugees. We thereby offer an agenda that will better serve public health needs, including those of migrants and refugees and advance equity in European health systems. - Funding - No specific funding received.
Online verfügbar 27 October 2023, Version des Artikels 27 October 2023
Gesehen am 02.02.2024